Epidemiology of herpes simplex virus type 2 in Asia: A systematic review, meta-analysis, and meta-regression - Sawsan AlMukdad, MSc; Manale Harfouche, MPH; Anja Wettstein, MSc; Laith J. Abu-Raddad, PhD (Elsevier, 2021)
Background: Herpes simplex virus type 2 (HSV-2) infection is a prevalent sexually transmitted infection worldwide. This systematic review was conducted to characterize HSV-2 epidemiology in Asia, including the World Health Organization regions of Southeast Asia and the Western Pacific. Methods: Cochrane and PRISMA guidelines were followed to systematically review and report findings. Pooled mean seroprevalence and proportions of HSV-2 isolated in genital ulcer disease (GUD) and in genital herpes were calculated using random-effects meta-analyses. Meta-regressions were also conducted. Quality assessment was performed. Findings: HSV-2 measures extracted from 173 publications included 15 seroconversion rates, 11 seroincidence rates, 272 overall seroprevalence measures (678 stratified), 14 proportions of HSV-2 isolation in GUD (15 stratified), and 27 proportions of HSV-2 isolation in genital herpes (36 stratified). Pooled mean seroprevalence was 12.1% (95% confidence interval (CI): 11.0-13.2%) among general populations, 23.6% (95% CI: 20.9-26.3%) among men who have sex with men and transgender people, 46.0% (95% CI: 39.2-52.9%) among HIV-positive individuals and individuals in HIV-discordant couples, and 62.2% (95% CI: 58.9-65.6%) among female sex workers. Among general populations, pooled mean seroprevalence increased gradually from 4.7% (95% CI: 3.3-6.3%) in <20-year-old individuals to 26.6% (95% CI: 19.2-34.7%) in >60-year-old individuals. Compared to women and across all populations, men had 0.60-fold (95% CI: 54.0-67.0) lower seroprevalence, that is women had 70% higher seroprevalence. Seroprevalence declined by 0.98-fold (95% CI: 0.97-0.99) per year, that is a 2% decline per year in the last three decades. Pooled mean proportions of HSV-2 isolation in GUD and in genital herpes were 48.2% (95% CI: 34.9-61.6%) and 75.9% (95% CI: 68.3-82.8%), respectively. Interpretation: Over 1 in 10 individuals is infected with HSV-2, but seroprevalence is declining. HSV-2 accounts for half of GUD cases and three-quarters of genital herpes cases. These findings support the need for an HSV-2 vaccine and universal access to sexual and reproductive health services.